2019
DOI: 10.21037/gs.2019.10.04
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for high-volume lymph node metastases in cN0 papillary thyroid microcarcinoma

Abstract: Background: Lymph node metastasis (LNM) often occurs in clinical lymph node negative (cN0) papillary thyroid microcarcinoma (PTMC). The risk factors for LNM, especially for high-volume LNM, were investigated in this study. Methods:The medical records of 1,974 consecutive PTMC patients admitted to the Peking Union Medical College Hospital (PUMCH) from 2013 to 2015 were reviewed. Their clinicopathological features were collected. Univariate and multivariate analyses were performed to identify the risk factors fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 36 publications
1
20
1
3
Order By: Relevance
“…Previous studies have demonstrated that male sex, age, multifocality, tumor diameter>0.5cm and ETE were independent risk factors for LNM in PTMC patients (8)(9)(10). In this study, univariate and multivariate analyses revealed that age <45 years and male gender are independent predictive factors for large-volume CLNM in cN0 PTC patients.…”
Section: Discussionsupporting
confidence: 51%
“…Previous studies have demonstrated that male sex, age, multifocality, tumor diameter>0.5cm and ETE were independent risk factors for LNM in PTMC patients (8)(9)(10). In this study, univariate and multivariate analyses revealed that age <45 years and male gender are independent predictive factors for large-volume CLNM in cN0 PTC patients.…”
Section: Discussionsupporting
confidence: 51%
“…[ 18 ] Recently, some studies also showed multifocality as the risk factor of high-volume (i.e., >5 metastatic lymph nodes) CLNMs in PTC. [ 23 , 29 ] However, multifocal lesions according to ultrasonography showed no significant relation with the presence of >5 CLNMs in cN0 ipsilateral PTC patients with tumor sizes 1 to 4 cm in our study. The results of our study were in accordance with those reported by Huang et al, wherein the multifocal lesions determined by preoperative ultrasound were not considered as risk factor for high-volume CLNMs in cN0 PTMC.…”
Section: Discussioncontrasting
confidence: 72%
“…Age is known to be an important prognostic factor for patients with PTMC. Previous studies have reported that younger age is an increased risk of CLNM [ 34 36 ] and high-volume (ie, >5 metastatic lymph nodes) CLNM [ 37 , 38 ] in cN0 PTMC patients. In addition, Miyauchi et al have reported that <40 years of age is the only significant risk factor for tumor size enlargement and novel appearance of lymph node metastasis of PTMC during active surveillance.…”
Section: Discussionmentioning
confidence: 99%
“…[ 41 ] However, men tend to more advanced disease diagnosed at an older age, lower disease-free survival, and higher mortality. [ 42 ] Previous studies have demonstrated that male sex is a significant risk factor for CLNM [ 34 36 ] and high-volume (ie, >5 metastatic lymph nodes) CLNM [ 37 , 38 ] in cN0 PTMC patients. Furthermore, Nixon et al have reported that male sex is the risk factor associated with central neck node recurrence in PTC patients without pCND.…”
Section: Discussionmentioning
confidence: 99%